Perfusion magnetic resonance imaging provides additional information as compared to anatomical imaging for decision-making in vestibular schwannoma - M.C. Kleijwegt; A.G.L. van der Mey; F.T. Wiggers-deBruine; M.J.A Malessy; M.J.P. van Osch (European Journal of Radiology Open, 2016)
Objective: The added value of perfusion MRI for decision-making in vestibular schwannoma (VS) patients is unknown. MRI offers two perfusion methods: the first employing contrast agent (dynamic susceptibility contrast (DSC)-MRI) that provides information on cerebral blood volume (CBV) and cerebral blood flow (CBF), the second by magnetic labeling of blood (arterial spin labeling (ASL)-MRI), providing CBF-images. The goal of the current study is to investigate whether DSC and ASL perfusion MRI provides complimentary information to current anatomical imaging in treatment selection process of VS. Methods: Nine patients with growing VS with extrameatal diameter >9 mm were included (>2 mm/year and 20% volume expansion/year) and one patient with 23 mm extrameatal VS without growth. DSC and ASL perfusion MRI were obtained on 3 T MRI. Perfusion in VS was scored as hyperintense, hypointense or isointense compared to the contralateral region. Results: Seven patients showed hyperintense signal on DSC and ASL sequences. Three patients showed iso- or hypointense signal on at least one perfusion map (1 patient hypointense on both DSC-MRI and ASL; 1 patient isointense on DSC-CBF; 1 patient isointense on ASL). All patients showed enhancement on post-contrast T1 anatomical scan. Conclusion: Perfusion MR provides additional information compared to anatomical imaging for decision-making in VS. Keywords: Vestibular schwannoma, Perfusion weighted MR, Decision making, Dynamic susceptibility contrast (DSC) and arterial spin labeling (ASL)